Koncepcja prawomocności orzeczeń sądów administracyjnych - Adamiak, Barbara (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
In order to develop the concept of finality of rulings issued by administrative courts, we need to take into account many factors. As a result, the issue of finality of rulings by administrative courts is more complex than the essence of finality of court rulings in civil and in criminal proceedings. Unlike civil and criminal proceedings, in which the right to trial is based on a uniform manner of administering justice by independ-ent courts of law and the Supreme Court, administrative court proceedings are part of a complex system that controls the work of public administration. The finality of ad-ministrative court rulings requires taking into account not only the right to trial but also the force of administrative court rulings with regard to the admissibility of con-trol of public administration in a different system of verification — verification by means of an administrative procedure
Keywords: sądy administracyjne; orzecznictwo; prawomocność orzeczeń; prawo skargi do sądu administracyjnego; kontrola działania administracji publicznej